A two-phase sequential approach to design bioenergy supply chains under uncertainty and social concerns. (February 2021) - Razm, Sobhan; Dolgui, Alexandre; Hammami, Ramzi; Brahimi, Nadjib; Nickel, Stefan; Sahebi, Hadi
Highlights: Developing models to design and planning of the bioenergy supply chains. Proposing a two-phase approach to solve the proposed models. Integrating geographical information, the social aspect, and the multi-criteria decision making techniques to find the appropriate locations for bio-refineries. Using robust optimization to hedge against uncertainty. Validating the two-phase approach by applying it to a case study. Abstract: The use of renewable energies has become very attractive, because it protects the environment and boosts regional development. In this paper, a sustainable two-phase sequential approach is proposed for the design of bioenergy SCs under uncertainties. The first phase, integrating geographical information, social aspects, and multi-criteria decision-making techniques, helps find appropriate locations for the bio-refineries. High rates of unemployment, and high vulnerability to the variation in the markets in an economic crisis are considered as social concerns. Integrating these factors filters the areas for the second phase. The first phase reduces complexity in the computation of the problem, and helps set up sustainable development in the supply chain. In the second phase, to cope with the uncertainties in the bioenergy supply network, a robust model is introduced. It reduces the sensitivity to inaccurate input data, and the obtained solutions stay optimal when the parameters change slightly. In order to validate this two-phase sequential approach, a case study is investigated. The results of tests show that integrating the concepts of uncertainties and sustainability with geographical information of the area in a two-phase sequential approach outperforms the traditional models, and leads to the creation of 262 jobs. The jobs have a high impact on the surrounding area.